2008
DOI: 10.1186/1471-2334-8-34
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infections in Italian Hospitals: a prospective multicenter study

Abstract: Background: Surgical site infections (SSI) remain a major clinical problem in terms of morbidity, mortality, and hospital costs. Nearly 60% of SSI diagnosis occur in the postdischarge period. However, literature provides little information on risk factors associated to in-hospital and postdischarge SSI occurrence. A national prospective multicenter study was conducted with the aim of assessing the incidence of both in-hospital and postdisharge SSI, and the associated risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
4
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 32 publications
5
78
4
5
Order By: Relevance
“…Also as this surgical technique was not commonly used in this hospital; the improper tissue handling during the procedure may be a contributory factor in increasing the risk of infection. In contrast to our finding Petrosillo et al 22 observed no significant difference in SSI rate between patients operated on for removal of the gallbladder by both techniques. 24 found by multivariable analysis both the above mentioned factors were independently associated with a higher risk of surgical site infection.…”
Section: Discussioncontrasting
confidence: 56%
“…Also as this surgical technique was not commonly used in this hospital; the improper tissue handling during the procedure may be a contributory factor in increasing the risk of infection. In contrast to our finding Petrosillo et al 22 observed no significant difference in SSI rate between patients operated on for removal of the gallbladder by both techniques. 24 found by multivariable analysis both the above mentioned factors were independently associated with a higher risk of surgical site infection.…”
Section: Discussioncontrasting
confidence: 56%
“…The overall infection rate in the present study compares favorably with a report from other researchers (12) whose overall infection rate was 22.7% and another report from the University of Nigeria Teaching Hospital, Enugu (13), with an infection rate of 27.98%. However, other researchers (14)(15)(16)(17)(18) reported lower overall infection rates at their various centers overseas. A lower infection rate was also reported in Nigeria (19).…”
Section: Discussionmentioning
confidence: 97%
“…The higher infection rate in emergency operation is attributed to inadequate preoperative preparation and the severity of the underlying condition that necessitated emergency procedure. 11,14,21 The number of people in the operating room theatre during surgery affected the infection rate. This increased with increase in the number of people.…”
Section: Discussionmentioning
confidence: 99%